The Implementation of Green Finance and Its Effectiveness Towards Banking Performance As Intermediaries Institution - Alessandro, Andreas; Maski, Ghozali; Pangestuty, Farah Wulandari (AIBPM Publisher, 2023)
The concept of sustainability arose in response to climate change during industrialization in the 18th century and has gained importance amid the Covid pandemic as nations aim for resilience. Indonesia, like other countries, needs a strong financial policy that integrates sustainability criteria. Banks, as trusted intermediaries, play a vital role in promoting ethical business practices and can contribute through initiatives like the SRI KEHATI index, which identifies environmentally friendly issuers based on ESG standards. The study analyzes the relationship between ESG-adjusted dividends and financial performance of four major Indonesian banks (KBMI) from 2011 to 2021, using panel data analysis. The findings indicate a negative relationship between adjusted dividends and return on assets (ROA), with similar patterns observed for ESG, environmental, and governance factors. However, the negative correlation is less prominent for the social factor. Conversely, adjusted dividends show a positive connection with ESG scores and the environmental, social, and governance factors independently.